Influence of protein extraction and texturization on odor‐active compounds of pea proteins. (7th August 2021) - Ebert, Sandra; Michel, Wiebke; Nedele, Ann‐Kathrin; Baune, Marie‐Christin; Terjung, Nino; Zhang, Yanyan; Gibis, Monika; Weiss, Jochen
Abstract: BACKGROUND: The use of plant proteins as food ingredients might be limited due to the presence of foreign or 'off' flavors, which may evolve during extraction and subsequent processing. In this study, the influence of dry (TVP) and wet (WTP) texturization on characteristic volatile compounds of two different pea protein isolates was assessed using gas chromatography–mass spectrometry‐olfactometry (GC–MS‐O) after direct immersion stir bar sorptive extraction (DI‐SBSE). RESULTS: Twenty‐four odor‐active compounds were found, with a prevalence of carbonyls from fat oxidation. Nine of these compounds which are also known as major (off‐) flavor contributors in peas were distinctively impacted in all texturates: hexanal, nonanal, 2‐undecanone, ( E )‐2‐octenal, ( E, Z )‐3, 5‐octadiene‐2‐one, ( E, E )‐2, 4‐decadienal, 2‐pentyl‐furan, 2‐pentyl‐pyridine, and γ ‐nonalactone. For example, hexanal, a characteristic green odorant, was reduced by up to sixfold by wet texturization, from 3.29 ± 1.05% (Pea Protein I) to 0.52 ± 0.02% (Pea WTP I). Furthermore, ( E, Z )‐3, 5‐Octadiene‐2‐one and ( E, E )‐2, 4‐decadienal were decreased by 1.5‐ and 1.8‐fold when Pea Protein I and Pea TVP I were compared. CONCLUSION: An overall reduction in fat oxidation products and of green and fatty odor‐active compounds was observed. The results represent a first insight into the process‐related modulation of pea protein (off‐) flavors to broaden the applicability of pea proteins as food ingredients.